Sounding Affective Consensus - Benjamin Barson (Journal of Extreme Anthropology, 2023)
This paper explores how New Orleans Black dockworkers created affective communities by utilizing brass bands, as evidenced by newspapers, union records, and testimonies from jazz musicians. In an attempt to weave together congruences between ‘history from below’, the affective turn, and theorists of the Black radical tradition, I argue that the nation’s largest Black Union in the late nineteenth century, the Longshoremen’s Protective Union Benevolent Association of New Orleans, successfully intervened in this port city’s economy by building a mass movement. They did so not only because of their strategic location in relation to capital and a modernizing logistics industry, but also because these dockworkers successfully struggled to control the affective modalities and temporalities of daily life. It was in this latter strategy that polyphonic brass bands and collective singing traditions played important roles in struggling for bodily autonomy and new social relations formulated in opposition to the profit motive. I coin this felt solidarity ‘affective consensus,’ which was a consensus-based decision-making process activated by agreed-upon musical conventions. Its power lies in its historical connections between democratic traditions of assembly, workplace struggles, and forms of participatory music making--all emblematic of late nineteenth-century Black New Orleans.